Effect of Repositioning Maneuver Type and Postmaneuver Restrictions on Vertigo and Dizziness in Benign Positional Paroxysmal Vertigo - Michel Toupet; Evelyne Ferrary; Alexis Bozorg Grayeli (The Scientific World Journal)
Introduction. To compare the efficiency of Epley (Ep) and Sémont-Toupet (ST) repositioning maneuvers and to evaluate postmaneuver restriction effect on short-term vertigo and dizziness after repositioning maneuvers by an analog visual scale (VAS) in benign positional paroxysmal vertigo (BPPV). Material and Methods. 226 consecutive adult patients with posterior canal BPPV were included. Patients were randomized into 2 different maneuver sequence groups (n=113): 2 ST then 1 Ep or 2 Ep then 1 ST. Each group of sequence was randomized into 2 subgroups: with or without postmaneuver restrictions. Vertigo and dizziness were assessed from days 0 to 5 by VAS. Results. There was no difference between vertigo scores between Ep and ST groups. Dizziness scores were higher in Ep group during the first 3 days but became similar to those of ST group at days 4 and 5. ST maneuvers induced liberatory signs more frequently than Ep (58% versus 42% resp., P<0.01, Fisher's test). After repositioning maneuvers, VAS scores decreased similarly in patients with and without liberatory signs. Postmaneuver restrictions did not influence VAS scores. Conclusion. Even if ST showed a higher rate of liberatory signs than Ep in this series, VAS scores were not influenced by these signs.